2008
DOI: 10.1037/0278-7393.34.4.823
|View full text |Cite
|
Sign up to set email alerts
|

A mental practice superiority effect: Less retroactive interference and more transfer than physical practice.

Abstract: Two experiments explored the benefits to retention and transfer conferred by mental practice. During familiarization, participants typed 4-digit numbers and took an immediate typing test on both old and new numbers. Participants then typed old 4-digit numbers, either physically or mentally, with either a different response configuration or the opposite hand from that used during familiarization. On a delayed test, participants physically typed both old and new numbers with the same response configuration and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
2
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 25 publications
11
69
2
18
Order By: Relevance
“…Please note that the two paradigms differed not only in terms of the retention delay (which differed by a factor of 43,200), but also in the presence/amount of interleaving events between encoding and retrieval. In the LTM version, participants were exposed to 24 h of new episodic experiences following encoding which might cause retroactive interference on the already acquired information [Wohldmann et al, 2008], whereas such retroactive interference was absent in the current study on immediate retrieval. The video clips were also shorter by a factor of about 250 compared to the 42‐min episode used in the LTM paradigm.…”
Section: Methodsmentioning
confidence: 99%
“…Please note that the two paradigms differed not only in terms of the retention delay (which differed by a factor of 43,200), but also in the presence/amount of interleaving events between encoding and retrieval. In the LTM version, participants were exposed to 24 h of new episodic experiences following encoding which might cause retroactive interference on the already acquired information [Wohldmann et al, 2008], whereas such retroactive interference was absent in the current study on immediate retrieval. The video clips were also shorter by a factor of about 250 compared to the 42‐min episode used in the LTM paradigm.…”
Section: Methodsmentioning
confidence: 99%
“…These results, of course, should not be taken as evidence against the elaborative retrieval account of the testing effect. They simply suggest that there may be other mechanisms-aside from enhanced verbal elaboration or semantic activation-that can contribute to the benefit of mentally reinstating information from memory (see Wohldmann, Healy, & Bourne, 2008, for an example of mental practice aiding motor skill learning). Also, our results dovetail nicely with findings from a recent study demonstrating that elaborative encoding does not interact with retrieval practice (Karpicke & Smith, 2010), suggesting that verbal elaboration may (in some situations) be orthogonal to the factors underlying the testing effect.…”
Section: Discussionmentioning
confidence: 99%
“…While mental practice has rarely been found to outperform PP, Wohldmann, Healy, and Bourne (2007) recently reported that these two types of practice could be equally effective to learn and maintain a new motor skill across a 3-month delay. In a second study, the same authors looked at the effect of a physical interference which was scheduled 1 and 2 weeks following the first learning phase (Wohldmann et al, 2008). The authors concluded that PP would strengthen an effector-dependent representation of the task, while MI should rather strengthen an effectorindependent representation.…”
Section: Discussionmentioning
confidence: 99%